2021
DOI: 10.1007/s12328-021-01555-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy of irritable bowel syndrome with anti-inflammatory cytokines

Abstract: Irritable bowel syndrome (IBS) is a multifactorial disease of which infection, as well as inflammation, has recently been considered as an important cause. Inflammation works as a potential pathway for the pathogenesis of IBS. In this review, we have discussed the targeted therapy of IBS. We used the search term “inflammation in IBS” and “proinflammatory” and “antiinflammatory cytokines and IBS” using PubMed, MEDLINE, and Google Scholar. The literature search included only articles written in the English langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 102 publications
0
6
0
1
Order By: Relevance
“…Anti-inflammatory effects of the algal sulfated polysaccharides were related to their sulfated content and proportion of monosaccharides. Previous reports suggested that the polysaccharides contain high amounts of the sulfate group, fucose, and galactose, which could inhibit the LPS-induced inflammatory response in RAW 264.7 cells [23][24][25][26][27]. CFCE-PS contains 21.06% sulfate and 70.19% galactose, and significantly inhibited the production of the inflammatory molecules in LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 93%
“…Anti-inflammatory effects of the algal sulfated polysaccharides were related to their sulfated content and proportion of monosaccharides. Previous reports suggested that the polysaccharides contain high amounts of the sulfate group, fucose, and galactose, which could inhibit the LPS-induced inflammatory response in RAW 264.7 cells [23][24][25][26][27]. CFCE-PS contains 21.06% sulfate and 70.19% galactose, and significantly inhibited the production of the inflammatory molecules in LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 93%
“…Our study found that the expression of inflammatory factors (IL-1β, IL-6, IL-8, IL-10, TNF-α) was elevated in the RS group. Some studies have shown elevated pro-inflammatory cytokines (IL-6, TNF-α) and decreased anti-inflammatory cytokine IL-10 in patients with IBS (Mitselou et al 2020;Kumar et al 2022), while others have shown no difference between patients with IBS and healthy controls (Kamp et al 2021). Although changes in inflammatory cytokine levels in IBS have been inconsistently reported, it has been shown that changes in cytokines may be associated with changes in the gut microbiota (Hustoft et al 2017;Zhou et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…5,76 A dysregulated mucosal inflammatory profile characterized by abnormal immune cells, increased proinflammatory cytokines and mast cells, as well as reduced expression of anti-inflammatory cytokines has been observed in IBS patients compared to controls. [77][78][79][80][81] One proposed model, backed by both preclinical and human data, suggests that the vagus nerve plays a central role by modulating the bidirectional gut-brain-microbiome axis via its anti-inflammatory properties. 21,31,82 The two most well-described pathways are the anti-inflammatory hypothalamic-pituitary-adrenal (HPA) axis and the vago-vagal cholinergic anti-inflammatory axis.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐grade chronic inflammation has been implicated and recent advanced immunohistochemical assays and ultrastructural analyses have demonstrated altered adaptive and innate immunity in IBS 5,76 . A dysregulated mucosal inflammatory profile characterized by abnormal immune cells, increased proinflammatory cytokines and mast cells, as well as reduced expression of anti‐inflammatory cytokines has been observed in IBS patients compared to controls 77–81 . One proposed model, backed by both preclinical and human data, suggests that the vagus nerve plays a central role by modulating the bidirectional gut–brain–microbiome axis via its anti‐inflammatory properties 21,31,82 .…”
Section: Discussionmentioning
confidence: 99%